Preventive Work on HIV Infection Among a Group of Minors (Texas Journal of Medical Science, 2022)
This article describes the preventive work carried out among groups of minors, which is mainly aimed at the formation and development of protective factors that prevent HIV infection. This applies to both biological (physiological) and psychological and social factors. Therefore, the leading principles of work in this group are programs for the formation of a healthy lifestyle for children and adolescents, their life skills, including communication skills, as well as preparation for difficult life circumstances.